2016
DOI: 10.1017/s1751731115002839
|View full text |Cite
|
Sign up to set email alerts
|

European conformation and fat scores have no relationship with eating quality

Abstract: 21European conformation and fat grades are a major factor determining carcass value 22 throughout Europe. The relationships between these scores and sensory scores 23 were investigated. A total of 3786 French, Polish and Irish consumers evaluated 24 steaks, grilled to a medium doneness, according to protocols of the "Meat Standards 25Australia" system, from eighteen muscles representing 455 local, commercial cattle 26 2 from commercial abattoirs. A mixed linear effects model was used for the analysis. 27There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 19 publications
4
25
0
4
Order By: Relevance
“…It may be concluded that the type of animal, fat class, conformation class, fat thickness and ossification score did not generally influence the quality of grilled meat to the extent to be perceived by consumers. A similar observation was made in the study of Bonny et al (2016), in which the juiciness prediction model was analysed. Neither of the analysed features (ossification score, animal age, marbling score, carcass weight, ultimate pH) was a good predictive variable.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…It may be concluded that the type of animal, fat class, conformation class, fat thickness and ossification score did not generally influence the quality of grilled meat to the extent to be perceived by consumers. A similar observation was made in the study of Bonny et al (2016), in which the juiciness prediction model was analysed. Neither of the analysed features (ossification score, animal age, marbling score, carcass weight, ultimate pH) was a good predictive variable.…”
Section: Discussionsupporting
confidence: 69%
“…In another research, McKenna et al (2004) stated similarly that consumer ratings for top loin steaks were not affected by USDA quality grade. Similarly, Bonny et al (2016) proved that there was almost no relationship between the European conformation score and untrained consumer sensory scores of quality for samples from France (45 cattle), Ireland (531 cattle) and Poland (54 cattle). This correlation could have resulted from the fact that the European conformation score (EUROP) assesses the whole carcass but not individual muscles.…”
Section: Discussionmentioning
confidence: 98%
“…In the European market, beef carcasses are valued on the basis of animal category (bull, steer, heifer, cow), carcass weight and the European carcass classification scores which is based on conformation and fat cover (E.U., 2008). However, this assessment has no relationship with the eating quality of beef (Bonny et al, 2016). New indicators have been proposed to improve the SEUROP classification such as meat colour (Monteils et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Many carcass classification systems for beef indirectly consider saleable meat yield [10,11] based on conformation, muscling, and fat depths in the hindquarter region, e.g., the EUROP carcass classification system or the fat depth by conformation matrix used in New Zealand [5,[12][13][14]. However, the carcass classification schemes for yearling cattle are generally undefined [2], and those used for older cattle are unlikely to be applicable due to a less developed conformation and fat deposition in yearling cattle [15].…”
Section: Introductionmentioning
confidence: 99%
“…Predictive models for saleable meat yield have not yet been developed for yearling steers. The boneless muscle weight from the hindquarter region has been used as an indicator of saleable meat yield for the whole carcass [12][13][14]24]. Hence, this study was initiated to identify the most pertinent explanatory variables for the weight of boneless cuts from the hind-legs of 8, 10, and 12 month old steers, and to develop predictive models which could be employed for both whole carcass classification and grading, thereby allowing the assignment of a carcass value.…”
Section: Introductionmentioning
confidence: 99%